Sewage mediated transfer of antibiotic resistance to River Yamuna in Delhi, India. Issue 1 (February 2020) - Lamba, Manisha; Sreekrishnan, T.R.; Ahammad, Shaikh Ziauddin
Graphical abstract: Highlights: Occurrence of antibiotic resistance in river Yamuna caused by sewage discharge. Poor sewage collection and lack of connectivity between drains and sewage treatment plants has worsen the situation. Critical pathogens listed by World Health Organisation in urgent need of new antibiotics were isolated from river Yamuna. Significant correlations between ARB and FC as well as ARGs and integron genes were observed. Abstract: Increase in antibiotic resistance (AR) in environment is a global health concern as the emergence of AR is limiting the treatment options. Inappropriate and indiscriminate uses of antibiotics are known causes for the spread of AR but lack of access to safe drinking water and poor sanitation aggravate the problem. The present study aims to estimate the abundance of coliforms, carbapenem and ESBL resistant bacteria and respective resistant genes in 20 sewer drains and 5 locations of the river Yamuna across New Delhi over two seasons. Significant positive correlations were observed between FC levels and carbapenem (R = 0.90, p = 0.002, n = 40) and ESBL resistant bacteria (R = 0.93, p = 0.005, n = 40) levels across all the samples, indicating possible association of resistant bacteria with faecal matter. However, higher abundances of coliforms, resistant bacteria and genes were observed in winter relative to summer season. Poor/lack of connectivity between drains and sewage treatment plants (STPs) and thus discharge of treated/untreated sewage at different locations of the river Yamuna is the major reason for increasing the pollution load of the river. Microbial culturing indicated presence of "critical pathogen" listed by WHO in urgent need of new antibiotics in the collected samples. Overall, release of untreated sewage into the river Yamuna carried by the sewer drains poses a high risk to the people residing in the city and highlights an urgent need to treat the entire sewage. Complete treatment of the entire sewage generated using treatment techniques such as advanced oxidation processes (80–90%) could reduce the introduction of these emerging pollutants in the environment.